The Anti-Inflammatory Activity of Toonaciliatin K against Adjuvant Arthritis - Lu, XinGang; Xue, JingWei; Shen, QiXing; Xu, XiaoLi; Wang, YiRu; Ye, Jie; Gou, HaiXing; Zhao, Jie (BioMed research international, 2017)
Toonaciliatin K is a natural limonoid purified from the Toona ciliata Roem. var. ciliata (Meliaceae). This study is to reveal the inflammatory suppression effect of toonaciliatin K and further the intrinsic mechanism. Firstly, anti-inflammatory effect of toonaciliatin K was evaluated in lipopolysaccharide- (LPS-) induced RAW264.7 cells. RT-PCR results indicated that the mRNA expressions of TNF-α, IL-6, and IL-1β were downregulated by toonaciliatin K. The toonaciliatin K inhibited TNF-α, IL-6, and IL-1β levels stimulated by LPS. Furthermore, LPS elicited the excess iNOS and COX-2 mRNA and protein production and toonaciliatin K attenuated the excess production. Western blot assay demonstrated that MAPK and NF-κB signaling pathways play critical roles in the toonaciliatin K’s anti-inflammatory activity. Secondly, toonaciliatin K inhibited carrageenan-induced paw edema in rats. Thirdly, toonaciliatin K alleviated the paw swelling and improved arthritis clinical scores in the adjuvant arthritis rats. Toonaciliatin K decreased the proinflammatory cytokines levels and Mankin scores in adjuvant arthritis rats. The HE staining, safranin O-fast green, and toluidine blue staining results demonstrated that toonaciliatin K alleviated the histological changes of paw, for example, pannus formation, focal loss of cartilage, bone erosion, and presence of extra-articular inflammation. Hence, toonaciliatin K is a promising agent for treatment of arthritis.